Shock index and pulse pressure as triggers for massive transfusion. Issue 1 (July 2019) - Zhu, Caroline S.; Cobb, Danielle; Jonas, Rachelle B.; Pokorny, Douglas; Rani, Meenakshi; Cotner-Pouncy, Tracy; Oliver, Jenny; Cap, Andrew; Cestero, Ramon; Nicholson, Susannah E.; Eastridge, Brian J.; Jenkins, Donald H.
Abstract : BACKGROUND: Hemorrhage is the most common cause of preventable death in trauma patients. These mortalities might be prevented with prehospital transfusion. We sought to characterize injured patients requiring massive transfusion to determine the potential impact of a prehospital whole blood transfusion program. The primary goal of this analysis was to determine a method to identify patients at risk of massive transfusion in the prehospital environment. Many of the existing predictive models require laboratory values and/or sonographic evaluation of the patient after arrival at the hospital. Development of an algorithm to predict massive transfusion protocol (MTP) activation could lead to an easy-to-use tool for prehospital personnel to determine when a patient needs blood transfusion. METHODS: Using our Level I trauma center's registry, we retrospectively identified all adult trauma patients from January 2015 to August 2017 requiring activation of the MTP. Patients who were younger than 18 years, older than 89 years, prisoners, pregnant women, and/or with nontraumatic hemorrhage were excluded from the study. We retrospectively collected data including demographics, blood utilization, variable outcome data (survival, length of stay, intensive care unit days, ventilator days), prehospital vital signs, prehospital transport times, and Injury Severity Score. The independent-samples t test and χ 2 test were used to compare the group who died to the group who survived. p < 0.05 was considered significant. Based on age and mechanism of injury, relative risk of death was calculated. Graphs were generated using Microsoft Excel software to plot patient variables. RESULTS: Our study population of 102 MTP patients had an average age of 42 years and average Injury Severity Score of 29, consisted of 80% males (82/102), and was 66% blunt trauma (67/102). The all-cause mortality was 67% (68/102). The positive predictive value of death for patients with pulse pressure of less than 45 and shock index of greater than 1 was 0.78 for all patients, but was 0.79 and 0.92 for blunt injury and elderly patients, respectively. CONCLUSIONS: Our data demonstrate a high mortality rate in trauma patients who require MTP despite short transport times, indicating the need for early intervention in the prehospital environment. Given our understanding that the most severely injured patients in hemorrhagic shock require blood resuscitation, this study demonstrates that this subset of trauma patients requiring massive transfusion can be identified in the prehospital setting. We recommend using Emergency Medical Services pulse pressure in combination with shock index to serve as a trigger for initiation of prehospital whole blood transfusion. LEVEL OF EVIDENCE: Therapeutic/care management, level V.